Correlation between Procalcitonin Values and Pneumonia Severity in Pediatric Patients - Yogi Zulkifli; Rini Savitri Daulay; Fera Wahyuni; Ranti Permatasari; Hendri Wijaya; Fathia Meirina (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pneumonia remains one of the leading causes of morbidity and mortality among children, particularly in developing countries. Rapid assessment of disease severity is essential for appropriate clinical management. Procalcitonin (PCT) is recognized as a biomarker of systemic bacterial infection; however, its role in determining the severity of pediatric pneumonia is still debated. This study aimed to analyze the correlation between procalcitonin levels and pneumonia severity in pediatric patient. This was an observational analytic study with a retrospective cross-sectional design using consecutive sampling. Data were collected from medical records of 102 pediatric patients aged 1 month to 18 years who were diagnosed with pneumonia throughout 2024. PCT levels were compared between children with severe pneumonia and those with severe pneumonia accompanied by danger signs. Statistical analysis included the Mann-Whitney test to assess differences in PCT values and ROC curve analysis to determine the optimal cut-off, sensitivity, specificity, and accuracy. The majority of patients (71.6%) presented with severe pneumonia with danger signs. PCT levels differed significantly between groups (p < 0.001). ROC analysis identified an optimal cut-off value of ≥1.06 µg/L, yielding a sensitivity of 82.2%, specificity of 79.3%, positive predictive value of 90.9%, negative predictive value of 63.9%, and overall accuracy of 81.37% (AUC = 0.874). There is a significant association between procalcitonin levels and the severity of pneumonia in children. Procalcitonin may serve as a valuable early biomarker for assessing disease severity and guiding clinical decision-making in pediatric pneumonia, particularly in healthcare settings in North Sumatra.